Exploring the Role of Polysemy Awareness for “Get” and “Make” in Podcasts on EFL Learners’ Collocational Speaking Ability - Amaliah, Suci; Baa, Sultan; Wahyuni, Ika Yuli; Mansyur, Mansyur; Sakkir, Geminastiti (ARRUS Journal of Social Sciences and Humanities, 2025)
This study examines the role of polysemy awareness of the verbs get and make through learning podcasts in improving EFL students’ collocational speaking ability. The basis of this study is the finding that the meaning variation of polysemous words often causes collocational errors in spoken language. At the same time, podcasts provide rich audio contexts that facilitate semantic comprehension. The study's objectives were to test the effectiveness of increasing polysemy awareness of collocational speaking accuracy and fluency and to explore the learning mechanisms of participants. The Mixed-Methods Sequential Explanatory Method was applied through a quantitative phase, pre-test and post-test of speaking collocations on 60 EFL students randomly divided into experimental and control groups, followed by a qualitative phase in the form of stimulated-recall interviews with 10 participants. The collocation assessment instrument showed high inter-rater reliability (α = 0.87). The quantitative results indicated a significant increase in accuracy (p < 0.05; d > 0.8) and a 20% increase in fluency scores in the experimental group. The qualitative findings revealed that participants utilized audio context clues to distinguish polysemous meanings before selecting collocations, shifting from a rote strategy to a contextual approach. In conclusion, integrating polysemy awareness in podcast materials effectively improves speaking collocational ability and strengthens the theory of contextual semantic learning. The implications of this study include the development of audio modules focused on polysemy semantics, teacher training, and further research on long-term retention and adaptation of materials based on proficiency.